1996
DOI: 10.1109/71.485506
|View full text |Cite
|
Sign up to set email alerts
|

A framework for designing deadlock-free wormhole routing algorithms

Abstract: Abstract-This paper presents a framework to design fully-adaptive, deadlock-free wormhole algorithms for a variety of network topologies. The main theoretical contributions are (a) design of new wormhole algorithms using store-and-forward algorithms, (b) a sufficient condition for deadlock free routing by the wormhole algorithms so designed, and (c) a sufficient condition for deadlock free routing by these wormhole algorithms with centralized flit buffers shared among multiple channels. To illustrate the theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…These virtual channels are used according to the Duato-Nbc routing scheme, which are divided into V 1 and V 2 classes (V = V 1 + V 2 ). This number of virtual channels yields the optimal performance compared to the other schemes proposed in [4].…”
Section: Model Assumptionsmentioning
confidence: 77%
See 2 more Smart Citations
“…These virtual channels are used according to the Duato-Nbc routing scheme, which are divided into V 1 and V 2 classes (V = V 1 + V 2 ). This number of virtual channels yields the optimal performance compared to the other schemes proposed in [4].…”
Section: Model Assumptionsmentioning
confidence: 77%
“…In [5], the Nbc routing scheme has been used in the context of Duato's methodology [6] and a routing algorithm, named Duato-Nbc with high performance and minimum virtual channel requirements was resulted. Investigations showed that Duato-Nbc has a better performance compared to other algorithms reported in the literature and the other algorithms proposed in [4].…”
Section: Adaptive Wormhole Routing In the Torus Networkmentioning
confidence: 92%
See 1 more Smart Citation
“…The structure of S n is a bipartite graph, and its nodes can be partitioned into two subsets; therefore, it can be coloured using only two colours [5]. Because adjacent nodes are in distinct partitions, the maximum number of negative hops a message may take is at most half the diameter of S n , which equals…”
Section: Adaptive Wormhole Routing In Star Graphsmentioning
confidence: 99%
“…In the negative-hop algorithm [5], the network is partitioned into several subsets, such that no subset contains adjacent nodes (this is equivalent to the wellknown graph colouring problem). If C is the number of subsets, then the subsets are labelled as 0, 1, …, C-1, and nodes in subset i are labelled (or coloured) as i.…”
Section: Adaptive Wormhole Routing In Star Graphsmentioning
confidence: 99%